2004
DOI: 10.1074/jbc.m403426200
|View full text |Cite
|
Sign up to set email alerts
|

The Schizosaccharomyces pombe Pccs Protein Functions in Both Copper Trafficking and Metal Detoxification Pathways

Abstract: Because copper is both an essential cofactor and a toxic metal, different strategies have evolved to appropriately regulate its homeostasis as a function of changing environmental copper levels. In this report, we describe a metallochaperone-like protein from Schizosaccharomyces pombe that maintains the delicate balance between essentiality and toxicity. This protein, designated Pccs, has four distinct domains. SOD activity assays reveal that the first three domains of Pccs are necessary and sufficient to deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 89 publications
1
38
0
1
Order By: Relevance
“…These results are particularly interesting considering that some organisms lack the D1 MXCXXC copper-binding motif, including Drosophila melanogaster and Anopheles gambiae (23) and the fission yeast Saccharomyces pombe (21). Because CCS from D. melanogaster is able to activate D. melanogaster SOD1 and ySOD1 fully without exhibiting copper chaperone activity (23), it appears that the primary function of CCS is that of a disulfide isomerase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are particularly interesting considering that some organisms lack the D1 MXCXXC copper-binding motif, including Drosophila melanogaster and Anopheles gambiae (23) and the fission yeast Saccharomyces pombe (21). Because CCS from D. melanogaster is able to activate D. melanogaster SOD1 and ySOD1 fully without exhibiting copper chaperone activity (23), it appears that the primary function of CCS is that of a disulfide isomerase.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these mechanisms is of critical importance because immature forms of SOD1 are believed to be linked to the neurodegenerative disease familial amyotrophic lateral sclerosis (14)(15)(16)(17). Although chaperoneindependent maturation of SOD1 has been reported in humans (hSOD1) (18,19) and other organisms (20)(21)(22)(23), the majority of the SOD1 activation within the cell, or 100% of activation in the case of yeast SOD1 (ySOD1), is via the SOD1-specific chaperone protein, copper chaperone for SOD1 (CCS) (24)(25)(26)(27)(28). CCS also likely exhibits disulfide isomerase activity (29,30).…”
mentioning
confidence: 99%
“…CCS has been characterized in fungi, animals, and plants (14,16,24,(53)(54)(55) indicating that this gene was present prior to the evolutionary divergence of eukaryotes and was subsequently lost in C. elegans. However, copper metabolism in C. elegans appears quite similar to other eukaryotes in many respects, and of the three known soluble copper carriers identified, C. elegans is missing only CCS.…”
Section: Discussionmentioning
confidence: 99%
“…It harbors an extra domain at the C terminus. Dr. Labbé and his colleagues have shown that the first three domains of Pccs are required to incorporate copper into SOD1 in the presence of low copper levels, whereas the fourth domain of Pccs functions to sequester metals under conditions of elevated copper concentrations [18] . These results describe the first example of a metalloprotein that functions as a copper chaperone when copper levels are low and as a detoxifier when copper levels are high.…”
Section: Discovery Of Fep1 An Iron Sensor That Represses Iron Transpmentioning
confidence: 99%